Auditing fungal disease in leukemia patients in a tertiary care center: opportunities and challenges for an antifungal stewardship program. Issue 10 (24th August 2019) - Paige, Emma; Haywood, Peter; Xie, Mingdi; Worth, Leon; Thursky, Karin; Urbancic, Karen; Bajel, Ashish; Slavin, Monica
Abstract: Invasive fungal disease (IFD) is responsible for significant morbidity and mortality in patients with acute leukemia. Antifungal stewardship (AFS) programs are utilized in this patient group but have been infrequently evaluated in clinical practice. Adults diagnosed with acute leukemia at an Australian tertiary center over two years were identified, with subsequent auditing of IFD prophylaxis and treatment, and identification of further opportunities for AFS activities. Proven or probable IFD occurred in 6% of cases, including 14% of acute lymphoblastic leukemia (ALL) patients and 6% of acute myeloid leukemia (AML) patients. Mold-active antifungal prophylaxis was used in 84% of cases overall, including in 94% of AML cases and 23% of ALL cases. Local auditing identified target areas for AFS in this complex patient cohort, including modification of clinical guidelines, enhanced patient screening, improved access to fungal diagnostics and therapeutic drug monitoring, and the establishment of a specialized, embedded AFS program.